Early detection and integrated care for adolescents and young adults with severe psychotic disorders: rationales and design of the Integrated Care in Early Psychosis Study (ACCESS III). Issue 1 (12th September 2016) - Lambert, Martin; Schöttle, Daniel; Sengutta, Mary; Ruppelt, Friederike; Rohenkohl, Anja; Luedecke, Daniel; Nawara, Luise Antonia; Galling, Britta; Falk, Anne‐Lena; Wittmann, Linus; Niehaus, Vivien; Sarikaya, Gizem; et al.
Abstract: Aim: The Integrated Care in Early Psychosis (ACCESS III) Study examined the efficacy and cost‐effectiveness of a combined intervention consisting of strategies to improve early detection and quality of care (integrated care including therapeutic assertive community treatment) in adolescents and young adults in the early phase of a severe psychotic disorder from 2011 to 2014. Methods: This is a prospective, single‐centre, 1‐year cohort study comparing an intervention condition (early detection plus integrated care, n  = 120) to the historical control condition (standard care, SC, n  = 105) for adolescents and young adults aged 12–29 years suffering from a severe, early‐phase psychotic disorder (i.e. within 2 years of treatment). Results: Primary outcome is the rate of combined symptomatic (i.e. Positive and Negative Syndrome Scale (PANSS) criteria) and functional (i.e. Global Assessment of Functioning scale (GAF) ≥ 60 points criterion) remission over at least 6 months at study endpoint. Secondary outcome comprises the comparison of the reduction in the duration of untreated psychosis within the 4‐year study duration between integrated care and SC, course of psychopathology, functioning, quality of life, satisfaction with care, cost and quality‐adjusted life years (QALYs) in comparison to a historical control group. Conclusion: To the authors' knowledge, this is the first study assessing the efficacy and cost‐effectiveness of a combined intervention consisting of early detection strategies and strategies to improve quality of care in both adolescents and young adults with early‐phase psychosis. The results will be published in 2016.